AGRESIFITAS ANAK KECANDUAN GAME ONLINE (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2018)
The internet offers a lot of convenience and comfort in human civilization. This can at least be seen in the digital economy, artificial intelligence, big data, robotic, and so on. Even so, the internet can also have a negative impact if the utilization is not appropriate. One of them is online games for children. Children who are addicted to online games tend to spend more time playing games than socializing with their peers. In addition, several online games also present content that is harmful to children's growth and development, such as pornography and violence. This study aims to analyze the addictive effects of online games on child aggressive. The approach used in this study is a quantitative approach. The results showed that addiction online game Mobile Legend: Bang-Bang has a significant effect on children's aggressiveness, with statistical data analysis results obtained that the higher the level of child addiction to online games, the higher the level of aggressiveness of the child.